Study of a Conical Plasma Jet with a Cloth-Covered Nozzle for Polymer Treatment - Kodaira, Felipe Vicente de Paula [UNESP]; Almeida, Ana Carla de Paula Leite [UNESP]; Tavares, Thayna Fernandes [UNESP]; Quade, Antje; Hein, Luis Rogério de Oliveira [UNESP]; Kostov, Konstantin Georgiev [UNESP] (MDPI, 2023)
Although atmospheric pressure plasma jets (APPJs) have been widely employed for materials modification, they have some drawbacks, such as the small treatment area (couple of cm2). To overcome this limitation, a funnel-like APPJ with a wide exit has been proposed. In this work, a gas-permeable cotton cloth covered the nozzle of the device to improve the gas flow dynamics and increase its range of operation. The funnel jet was flushed with Ar, and the plasma was ignited in a wide range of gas flow rates and the gap distances between the exit nozzle and the sample holder. The device characterization included electric measurements and optical emission spectroscopy (OES). To evaluate the size of the treatment and the degree of surface modification, large samples of high-density polyethylene (PE) were exposed to plasma for 5 min. Afterward, the samples were analyzed via water contact angle WCA measurements, scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). It was found that surface modification occurs simultaneously on the top and bottom faces of the samples. However, the treatment incorporated different functional groups on each side.
Keywords: APPJ; atmospheric plasma; conical APPJ; polymer treatment; surface modification